Sustainability in the textiles & clothing fashion industry: an ongoing study in Portugal - Broega, A. C. (2019)
The waste from fashion is a problem that has significantly increased due to the growth of "fast fashion", pushed by increasing efficiency in production, logistics and Marketing encouraging consumers to have more clothes and discard them more quickly. Despite today’s aesthetic needs, Design has an urgent ethical obligation to incorporate sustainability in the decision making process. This will be a positive contribution to the global environmental, social and economical agenda. The challenge of professional designers is twofold, as they must meet increasingly complex requirements of a changing society and, at the same time, contribute to achieve sustainability throughout the entire Product Life Cycle. Such challenge faces a lack of competency among designers regarding sustainability, and a number of barriers including the poor externalization of sustainability costs, lack of customer awareness and effective legislation. In this paper we intend to present an overview of sustainability practices in the Portuguese Fashion Industry (Textiles & Clothing) starting with a brief characterization of the sector, followed by perspectives of sustainable consumption practices in Portugal. Finally some successful brands cases, of good practice in the framework of sustainable strategies are presented. These cases are based on small new business models essentially related to Fashion Design products. Significantly the practices present the choice for more sustainable materials, with many brands adopting organic, recyclable or/and biodegradable, and/or cruelty-free options. Another angle is related to up-cycling, increasing the Life Cycle of materials and/or garments by re-designing it. Many brands or even organizations or companies play on the values of "Ethical Fashion for sustainability" which is based on "social and cultural responsibility” (working for social development (mainly artisans) through the contribution given to improving the quality of life of those involved, for cultural, economic and social enrichment). Environmental sustainability is the most talked about and prioritized at the industrial level. However, the promotion of Fair Work/Trade, aiming of create professional training and opportunities for local communities to ensure good working conditions, environment and cultures respect is also valued in this sector. In conclusion, we highlight the need for brand communication. The Portuguese brands with good practices in the area of sustainability need to communicate their values in a transparent and systematic way, as it is not enough to make the effort to become sustainable, it is necessary to know how to communicate these values.